The centrality of partnership between local congregations and Christian development organisations in facilitating holistic praxis - Celesi, Mawonga P. (HTS teologiese studies, 2019)
Central to the argument of this article is the view that enhanced partnership between local congregations and Christian development organisations has the potential to facilitate holistic congregational praxis. In most cases, these entities of the church are found in the same locality, and therefore, need to define how they can together play a bigger and meaningful role in the transformation of their community. Bound by their faith mandate, working together as partners as opposed to competing with each other, they will find strength in each other and portray a good image of the Christian community in society. Guided by partnership ethos of trust, equality and mutual respect, they can both play a leading role in the nation-building project of South Africa. The article therefore explores the findings of the ‘Faith Matters’ study with regard to the relationship between local congregations and Christian development organisations and seeks to make recommendations with regard to ways in which this partnership could be strengthened.